1964
DOI: 10.3133/pp429b
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of benthonic species

Abstract: The faunal composition of zones A, D, E, and F off Central America is similar to that of equivalent zones off California; zones B and C are characterized by different species in the two regions. Zonal boundaries are at greater depths off California than off El Salvador. Physical and chemical factors that appear to influence distribution of Foraminifera are: depth; temperature, salinity, and oxygen content of the water; and nitrogen content and grain size of the bottom sediments. Salinity and oxygen values are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 4 publications
0
23
0
Order By: Relevance
“…Although these taxa are also found at Site 999, other common Caribbean taxa (e.g., C. wuellerstorfi) do not occur at the Pacific site. Shallower tropical Eastern Pacific biofacies as described by Smith (1964) and McDougall (1985) seem no more comparable to the Caribbean Site 999 biofacies, so we have compared the general lower bathyal-abyssal biofacies from each side of the Panamanian isthmus (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Although these taxa are also found at Site 999, other common Caribbean taxa (e.g., C. wuellerstorfi) do not occur at the Pacific site. Shallower tropical Eastern Pacific biofacies as described by Smith (1964) and McDougall (1985) seem no more comparable to the Caribbean Site 999 biofacies, so we have compared the general lower bathyal-abyssal biofacies from each side of the Panamanian isthmus (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…The generic classification of Loeblich and Tappan (1988) was used. The depth distribution of benthic foraminifers is based on recent ecological data of Bandy and Arnal (1957), Crouch and Poag (1987), Heinz et al (2008), and Smith (1963Smith ( , 1964 reported from the Pacific off Central America.…”
Section: Benthic Foraminiferal Taxonomy and Paleodepth Determinationmentioning
confidence: 99%
“…Characteristic genera of these environments include Uvigerina , Bulimina , Globobulimina , Brizalina and Bolivina , which frequently occur in eutrophic and oxygen‐limited ecosystems such as oxygen minimum zones at intermediate water depths (Sen Gupta and Machain‐Castillo, 1993; Bernhard and Sen Gupta, 1999). Off Middle America the modern‐day oxygen minimum zone extends from approximately 400 to 900 m (Smith, 1964).…”
Section: Benthic Foraminifera As Palaeodepth Indicatorsmentioning
confidence: 99%
“… References: 1 Smith (1964); 2 McDougall (1985); 3 Pflum and Frerichs (1976); 4 Lutze (1980); 5 Schmiedl et al . (1997); 6 Schiebel (1992); 7 Mead (1985); 8 Bornmalm (1997); 9 Corliss (1979); 10 Ingle and Keller (1980); 11 Sen Gupta and Machain‐Castillo (1993); 12 Corliss (1985); 13 Rathburn and Corliss (1994); 14 Mackensen et al .…”
Section: Bathymetric Significance Of Foraminiferal Assemblagesmentioning
confidence: 99%